GREY DIRECTORS ATTRIBUTE AND IDIOSYNCRATIC RISK OF LISTED MANUFACTURING FIRMS IN NIGERIA (Journal of Global Accounting, 2025)
The study investigated the nexus between grey directors’ attribute and idiosyncratic risk of listed manufacturing firms in Nigeria using a ten (10) year time frame that span through 2014 to 2023. To achieve the stated broad objectives, specific attributes of grey directors’ which have been widely employed in related extant literature to include, grey director nationality, and grey director overlap function were selected to ascertain the extent to which they affect idiosyncratic risk. This study employed ex-post facto and descriptive research design on a panel data set sourced from annual financial reports of a sample of forty-six listed manufacturing firms in Nigeria. Further, Iterated Generalized Least Squares (IGLS) Random Effects with Heteroskedastic Panels regression model was employed to test the formulated hypotheses. The findings revealed that grey director attributes and overlapping roles did not exhibit significant relationship with firm-specific risk, nationality of grey directors showed a strong negative relationship with idiosyncratic risk. Therefore, based on the foregoing empirical outcomes, this study recommends among others that stakeholders in the manufacturing industry should refrain from formulating or implementing governance reforms solely on the assumption that dual-role occupancy inherently enhances risk oversight.
Keywords: Grey Director Nationality; Grey Director Overlap; Idiosyncratic Risk